Middle East and North Africa Economic Monitor, October 2016 : Economic and Social Inclusion to Prevent Violent Extremism - Devarajan, Shantayanan; Mottaghi, Lili; Do, Quy-Toan; Brockmeyer, Anne; Joubert, Clement; Bhatia, Kartika; Abdel-Jelil, Mohamed (Washington, DC: World Bank, 2016)
The year 2016 appears to be one of the toughest for the Middle East and North Africa (MENA) region as their governments face serious policy challenges. The biggest challenge for oil exporters is managing their finances and diversification strategies with oil below $45 a barrel. Fiscal consolidation in a difficult sociopolitical environment and spillovers from conflicts are creating challenges for oil importers as well. Real GOP growth in MENA for 2016 is projected to fall to its lowest level since 2013 -- 2.3 percent -- lower than last year's growth by half a percentage point and about one percentage point lower than predicted in April 2016.